The Influence of Operation Strategy on Culinary Business Performance in Malang City - Fien Zulfikarijah (Journal of International Conference Proceedings (JICP), 2018)
This study aims to analyze and examine the effect of operating strategies on culinary business performance in Malang which is currently developing rapidly. This research is very important in developing culinary business in Malang by first knowing the operation strategy and culinary business performance and then analyzing the effect of operating strategies on culinary business performance both simultaneously and partially. The total population of the study was 67 managers with the criteria applying the halal concept, from the total population only 30 respondents filled out the questionnaire completely. Operating strategy variables use cost, quality, flexibility and delivery. Data analysis was performed using a range of scales and multiple regression. The results showed that the first operating strategy and culinary business performance were generally very good, both operating strategies had an effect on culinary business performance, meaning that the more appropriate the operating strategy applied would be the better the culinary business performance. Quality variable has dominant influence on culinary business performance, which means culinary efforts emphasize quality over cost, flexibility and delivery. Keywords : Operation Strategy, performance